Scedosporium apiospermum as a rare cause of central skull base osteomyelitis. - Jalava-Karvinen P; Nyman M; Gardberg M; Harju I; Hohenthal U; Oksi J (ELSEVIER SCIENCE BV, 2025)
We report a case of Scedosporium apiospermum mold causing ear infection, central skull base osteomyelitis and finally, occlusion of carotid artery in a 48-year-old diabetic man. The exact diagnosis was established and the severity of the disease understood several months after the onset of symptoms. Despite of appropriate antifungal therapy, and repeated surgical and otological procedures, the infection progressed to fatal cerebral infarction.